Esophagectomy in a patient with double aortic arch and right descending aorta. (March 2019) - Clement, Elizabeth A; Laing, Bryce; Turner, Simon R
We herein report the case of a 57-year-old man with esophageal cancer who was found to have a double aortic arch and right-sided descending aorta. Traditional approaches such as the Ivor Lewis and McKeown were excluded because the descending aorta would obscure the surgical field, and a neck anastomosis with the conduit through the ring could result in compression. We therefore opted for a left thoracoabdominal incision, allowing excellent exposure while reserving the possibility of placing the conduit substernally.